2014
DOI: 10.4081/ija.2014.556
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the use of plastic protective covers in field grown melon on a farm scale

Abstract: This in-farm research study was aimed at evaluating new strategies in the use of plastic protective covers in field grown melon in order to expand the production period and reduce costs. Four experiments were set up in 2010 and repeated in 2011 in Central Italy, in an inland region with a temperate climate. We evaluated: i) the use of high tunnels for two growing cycles per year, i.e. for very early and very late production (target transplanting in late winter and mid-summer, respectively), for either one year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
7
0
2
Order By: Relevance
“…The moderate reduction of melon marketable yield observed in ORG compared to CONV is in line with the overall 20% reduction reported by Thorup-Kristensen et al (2012) for organically grown vegetables compared to conventionally grown ones in a mixed rotation with cereals. Nonetheless, the yields we recorded in ORG were similar to those reported by Song et al (2010) and higher than those obtained by Benincasa et al (2014) for muskmelon grown conventionally in a similar environment.…”
Section: Discussionsupporting
confidence: 87%
“…The moderate reduction of melon marketable yield observed in ORG compared to CONV is in line with the overall 20% reduction reported by Thorup-Kristensen et al (2012) for organically grown vegetables compared to conventionally grown ones in a mixed rotation with cereals. Nonetheless, the yields we recorded in ORG were similar to those reported by Song et al (2010) and higher than those obtained by Benincasa et al (2014) for muskmelon grown conventionally in a similar environment.…”
Section: Discussionsupporting
confidence: 87%
“…A number of studies have recently analysed the agronomic and environmental performance of paper mulch (Martin-Closas et al, 2003;Moreno et al, 2013;Haapala et al, 2014), polyethylene with additives for degradation or biodegradable films (Filippi et al, 2011;Saraiva et al, 2012;Benincasa et al, 2014). By conducting field experiments, these studies showed that these potential substitutes of conventional films offer the advantage of degrading into non-toxic components.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by Kosterna et al [21] and Majkowska-Gadomska [8] showed that flat covers used under moderate climate conditions helped to obtain satisfactory yields of ripe melon fruits even when the summer months were characterized by lower air temperatures. Also, Benincasa et al [22] found in their study, conducted in central Italy, a 12% increase in melon yield as a result of covering. However, Gordon et al [23], who carried out their study in a subtropical humid climate, reported a 30% decline in pumpkin yield due to cover application compared with cultivation without covering.…”
Section: Discussionmentioning
confidence: 99%